Elaboration of bovine manure biodigester for biogas transformation to electric power - Giler, Jonathan Javier García; Cedeño, Cristopher Nazario Ponce (International research journal of management, IT and social sciences, 2020)
This research concerns the design of a biodigester to obtain biogas from organic cattle, which seeks to reduce waste contamination. By describing the descriptive-experimental method and bibliographic collection of previous studies, information was collected where the manure sample of 6 cows for 5 consecutive days obtaining an average of 7.5 Kg per day, Also, two practical biodigesters were built in this study using two 20L drums, pipes and valves, the first called biodigester experimental, which was monitored during the time of stay of the substrate in which temperature data was collected, specimen and flame tests were performed during the biogas generation process. Tubular biodigester design formulas vacuum were applied to project experimental results to a total of 15 cattle heads and thus obtain overall results by which the experimental biodigester was chosen. It was concluded that the production of methane gas is 2.83 m3 per day, which would provide 45% of the total value needed by the Breeding ground to cover activities in which it uses liquefied petroleum gas (LPG).